THE ROLE OF INNOVATIVE TECHNOLOGIES IN MANAGEMENT IN ADVANCING THE GREEN ECONOMY (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This article analyzes the theoretical and practical aspects of developing a green economy through the use of innovative technologies in the management system. The importance of innovative management tools in increasing economic efficiency, rational use of resources, ensuring energy saving, and strengthening environmental sustainability is highlighted. In addition, the impact of digital technologies, automated management systems, and environmental monitoring tools on the development of the green economy is studied. As a result of the research, priority directions of innovative approaches for the development of the green economy in the country are substantiated